Code-switching : bilingual incompetence or effective communicative strategy? - Leong, Kwan Yi (2011)
Like other multilingual contexts, code-switching has become a recognised norm in the verbal interaction of Malaysian bilingual speakers. There have been a plethora of studies published on the reasons for code-switching. Of late, contemporary studies have generally attributed code-switching to social and stylistic aspects. In spite of that, little seemed to discuss the traditional view of idealised bilingualism which suggested that code-switching is used to compensate for bilingual incompetence. This study examines the most preferred reason for code-switching by exploring both the traditional and contemporary aspects among bilingual English Language undergraduates in Universiti Tunku Abdul Rahman. Using a mix of quantitative and qualitative methods, the data is obtained through a questionnaire and interviews with selected participants. The findings presented here also incorporate details such as the respondents’ linguistic repertoire and their attitudes towards code-switching. But mainly, it shows that the most preferred reasons for codeswitching is not proficiency-based but ultimately, socially and stylistically motivated.